Pengelolaan Website di Lembaga Pendidikan - Fachri Naufaldi (Communications, 2019)
Website management is one of the new task in Public Relations On The Net era. Public Relations in educational institutions also do website management activities one of them is Public Relations of SMAN 31 Jakarta. In this research discusses about website www.sman31jakarta.sch.id management. This website management got complaints from students of SMAN 31 Jakarta about lack of academic activities information on website. So, the author want to see how the website management in educational institutions about lack of academic activities information on website www.sman31jakarta.sch.id? In this research, the author use the concept of Public Relations On The Net with variable website management. This variable has six dimensions such as the links must be online, available contact information, arrangement of information placement, coloring, easy to use and aims. This research use quantitative approach with descriptive research type and use survey method. The research held at SMAN 31 Jakarta. Author use a questionnaire with interval scales. Populations in this research are 1.067 students, and the samples are 234 students of SMAN 31 Jakarta obtained from the formula slovin. The sampling technique is stratified sampling and central tendency is mean. Validity test use KMO-MSA (Kaiser mayer olkin-measure of sampling adequany) and Barlett Test. Reliability test use Chronbach’s Alpha. In this research, there is a dimension with the highest mean which is coloring (use of color). The dimensions are obtained the lowest mean value is every link offered must be online (no dead links). Indicator with the highest mean value is using colors that facilitate the content of messages in the website screen easy to read. Indicator with the lowest mean value is does not disappointed the user This is because of the website visitors do not get complete information on the website www.sman31jakarta.sch.id. Based on the results of this research can be known website www.sman31jakarta.sch.id have been well in color selection which make it easier for website visitors. However, the website www.sman31jakarta.sch.id has not been maximized in providing information especially information about academic activities.